PENGARUH PENGELUARAN PEMERINTAH BIDANG PENDIDIKAN DAN KESEHATAN TERHADAP IPM KABUPATEN SUMBAWA TAHUN 2015-2020 - Abdul Rahim; Marisa Sutanty; Putri Anggita (Pusat Riset dan Publikasi, 2021)
This study aims to know the effect of government spending in education and health toward Human Development Index (IPM) in Sumbawa District.The data used in this study was time series data for 5 years from 2015 to 2020. The type of this study was associative that uses quantitative data.The data sources used was secondary data obtained from the Finance and Asset Management Agency Regions (BPKAD). The technique used to analyze data were multiple linear regression, t test, f test and R2. The results of study showed that the variable of government spending in education had an effect toward the human development index as indicated by t-value was higher than t-table (4.462 > 3.182, then variable of government spending in health partially had effect toward the human development index, indicated by the t-value was higher than t-table (4.566 > 3.182. Furthermore, government spending in education and health simultaneously had effect toward human development index of Sumbawa District, this was based on the result of f-value was higher than f-table (17.762 > 9.55) with significance value of 0.022 <0.05. The value of R2 was 0.922 which means that the effect of government spending in education and health toward human developmentindex (IPM) in Sumbawa District in year of 2015-2020 was 92.2% while its remaining of 7.8% was affected by other variable out of this study.